2005
DOI: 10.1055/s-2005-870188
|View full text |Cite
|
Sign up to set email alerts
|

Alfatradiol (0,025 %) - Eine wirksame und sichere Therapieoption zur Behandlung der androgenetischen Alopezie bei Frauen und Männern

Abstract: Androgenetic alopecia (AGA), also referred to as male pattern baldness, is the most common cause of hair loss in both sexes in adulthood. An option for topical treatment that selectively tar− gets the metabolic pathways involved in the balding process is alfatradiol, an estrasterid without hormonal activity. In a drug monitoring study, efficacy and safety of alfatradiol (0.025 %) was assessed in 233 patients with AGA (192 women, aged 14 ± 76 years, and 41 men, aged 17 ± 56 years). After 7.5 months of treat− me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
1
2
0
1
Order By: Relevance
“…Due to study by Wozel et al 23 , alfa-tradiol is involved more in stabilization or deceleration of hair loss, which is consistent with the results found in the previous placebo-controlled study of 51 patients (9 women) over 6 months by Van Neste and Rushton 24 .…”
Section: Discussionsupporting
confidence: 85%
“…Due to study by Wozel et al 23 , alfa-tradiol is involved more in stabilization or deceleration of hair loss, which is consistent with the results found in the previous placebo-controlled study of 51 patients (9 women) over 6 months by Van Neste and Rushton 24 .…”
Section: Discussionsupporting
confidence: 85%
“…Various experiments have shown that, in comparison with 17β-estradiol, 17α-estradiol did not exhibit estrogen activity or exhibited only very weak activity. In the treatment of androgenetic alopecia, the action mechanism of 17α-estradiol is to suppress 5α-reductase activity, which impedes the conversion of testosterone to the more potent metabolite DHT 5 , 22 , 23 . In addition, it inhibits 17β-dehydrogenase activity, resulting in a slowing of the conversion process of androstenedione to testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…In a controlled, randomized double-blind study, 63% of the treated patients with 17α-estradiol showed a reduction of the amount of telogen hairs, whereas in the control group the same reduction was found in only 37% of the cases 23 . Wozel et al 22 reported that 17α-estradiol increases and maintains the rate of anagen hair in 88% of the treated patients. When compared with minoxidil 17α-estradiol showed relatively lower efficacy compared to minoxidil in hair density and thickness 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Neben Minoxidil wird auch 17α-Estradiol (Alfatradiol) lokal eingesetzt, allerdings gibt es zu dieser Substanz nicht genug wissenschaftliche Studien [7,8].…”
Section: Lokale Therapieunclassified